Pengaruh Umur Terhadap Persentase Karkas dan Non Karkas Pada Ternak Kerbau - Amri, Ulil; Iskandar, Iskandar (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2014)
The objective of this experiment was to reveal carcass and non-carcass percentage of male buffalo slaughtered at Slaughter House, Jambi. There were 60 male buffalo consist of 30 male buffalo with two pair of Incicifus (I2) and 30 male buffalo with four pair of pasang Incicifus (I4). Parameters measured were slaughter weight, carcass weight and non-carcass weight. Results of this experiment showed that the slaughter weight of buffalo at age I2 and I4 were 338. 56±18.5 kg and 387.48±45.5 kg respectively, the carcass weight at age I2 and I4 were 148.56 kg 169.36 kg respectively and the non-carcass weight at age I2 and I4 were 137.40 kg and 157.19 kg respectively. The carcass percentage for I2 and I4 were 43.89 and 43.72 % respectively and the non-carcass percentage for I2 and I4 were40.58 and 40.57 % respectively. It could be concluded that the age effect was not significantly different (P >0,05) on the carcass percentage carcass and non-carcass percentage on male buffalo.